Progress on the development of Class A GPCR-biased ligands - Morales, Paula; Scharf, Magdalena M; Bermudez, Marcel; Egyed, Attila; Franco, Rafael; Hansen, Olivia K; Jagerovic, Nadine; Jakubík, Jan; Keserű, György M; Kiss, Dóra Judit; Kozielewicz, Pawel; Larsen, Olav; et al. (British journal of pharmacology, 2025)
Class A G protein-coupled receptors (GPCRs) continue to garner interest for their essential roles in cell signalling and their importance as drug targets. Although numerous drugs in the clinic target these receptors, over 60% GPCRs remain unexploited. Moreover, the adverse effects triggered by the available unbiased GPCR modulators, limit their use and therapeutic value. In this context, the elucidation of biased signalling has opened up new pharmacological avenues holding promise for safer therapeutics. Functionally selective ligands favour receptor conformations facilitating the recruitment of specific effectors and the modulation of the associated pathways. This review surveys the current drug discovery landscape of GPCR-biased modulators with a focus on recent advances. Understanding the biological effects of this preferential coupling is at different stages depending on the Class A GPCR family. Therefore, with a focus on individual GPCR families, we present a compilation of the functionally selective modulators reported over the past few years. In doing so, we dissect their therapeutic relevance, molecular determinants and potential clinical applications. LINKED ARTICLES: This article is part of a themed issue Complexity of GPCR Modulation and Signaling (ERNST). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v182.14/issuetoc.
Keywords: lidé; Humans; Drug Discovery; Drug Development; G protein‐coupled receptors; signální transdukce; vyvíjení léků; Ligands; receptory spřažené s G-proteiny; GPCR modulators; Receptors, G-Protein-Coupled; biased signalling; ligandy; Signal Transduction; zvířata; functionally selective ligands; Animals; objevování léků